2021
DOI: 10.3389/fcell.2021.624711
|View full text |Cite
|
Sign up to set email alerts
|

Single-Cell RNA Sequencing With Combined Use of Bulk RNA Sequencing to Reveal Cell Heterogeneity and Molecular Changes at Acute Stage of Ischemic Stroke in Mouse Cortex Penumbra Area

Abstract: Stroke has been the leading cause of adult morbidity and mortality over the past several years. After an ischemic stroke attack, many dormant or reversibly injured brain cells exist in the penumbra area. However, the pathological processes and unique cell information in the penumbra area of an acute ischemic stroke remain elusive. We applied unbiased single cell sequencing in combination with bulk RNA-seq analysis to investigate the heterogeneity of each cell type in the early stages of ischemic stroke and to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
41
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 44 publications
(54 citation statements)
references
References 47 publications
6
41
0
Order By: Relevance
“…In agreement, Guo et al. 52 recently profiled the single-cell transcriptional analysis of the mouse brain cortex penumbra area 24 h after MCAO, which identified 13 major cell types, each showing similar gene expression patterns to our study. However, the composition ratio of the cell types was different between the two studies (Guo et al.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…In agreement, Guo et al. 52 recently profiled the single-cell transcriptional analysis of the mouse brain cortex penumbra area 24 h after MCAO, which identified 13 major cell types, each showing similar gene expression patterns to our study. However, the composition ratio of the cell types was different between the two studies (Guo et al.…”
Section: Discussionsupporting
confidence: 92%
“…Hence, cell-type specific regulatory genes, especially those involved in subcluster associated diseases, should be considered for biomarkers in stroke, and ischemic insult caused alteration of DEGs across multiple cell types may have a potential implication for the intervention. In agreement, Guo et al 52 recently profiled the single-cell transcriptional analysis of the mouse brain cortex penumbra area 24 h after MCAO, which identified 13 major cell types, each showing similar gene expression patterns to our study. However, the composition ratio of the cell types was different between the two studies (Guo et al versus our study), probably owing to several reasons, including in the subclusters classification of cell types, the different brain tissues sampled (cortex penumbra versus cerebral hemisphere), varying enzymatic methods for tissue dissociation and whether samples were mixed or not for library construction (yes versus no) and so on.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…5 C). This phenotype has also been reported in stroke and many other diseases [ 50 , 52 , 53 ], indicating the inflammatory disease-associated phenotypes of MG 1/3 cluster. Strikingly, MG 3 cluster also demonstrated upregulated expression of Itgax, Lyz2 (Fig.…”
Section: Resultssupporting
confidence: 69%
“…Particularly, Hasel’s recent single-cell sequencing of LPS-induced RAs revealed that RAs could be divided into nine subpopulations with distinct gene expression and some subgroups appear in different CNS diseases ( Hasel et al, 2021 ). In the study of ischemic stroke, astrocytes in ischemic penumbra can be divided into seven subgroups and proposed related pathological mechanisms and therapeutic targets ( Guo et al, 2021 ). The spatiotemporal heterogeneity of RAs brings us many questions.…”
Section: Reactive Astrocytesmentioning
confidence: 99%